Towards a postmodern synthesis of Islamic science and modern science: The epistemological groundwork - Bakar, Osman (The Royal Islamic Strategic Studies Centre, 2019)
The main purpose of this article is to provide an introductory discussion of one of several knowledge synthesis projects with which I have been engaged in the past one decade. I call this particular project “Postmodern Synthesis of Islamic Science and Modern Science.” For clarity about the whole purpose of this project, an explanation of the terms in the title seems necessary. Let me first explain the meaning of the term ‘Islamic science’ in the sense I am using it here. A clarification of the term would help us to focus on the real issues that are raised by the title of this essay, since in current usage the term is found to connote several different meanings, and hence the possibility of confusion. Some people are using the term Islamic science as an English rendering in singular of the Arabic al-‘ulum al-Islamiyyah that primarily refers to the so-called religious sciences, especially the sciences of the Quran and Prophetic hadiths, science of principles of religion (‘ilm usul al-din), and sciences of Islamic jurisprudence (‘ilm al-fiqh) and principles of jurisprudence (‘ilm usul al-fiqh). From the point of view of Islamic epistemology, the term al-‘ulum al-Islamiyyah as understood by a large segment of the ‘ulama’ is found to be inherently problematic.